Variability of amethyst mining waste: A mineralogical and geochemical approach to evaluate the potential use in agriculture. (10th February 2019) - Korchagin, Jackson; Caner, Laurent; Bortoluzzi, Edson Campanhola
Abstract: Large amounts of stone wastes are accumulated alongside different exploiting mines of amethyst geodes in south Brazil, which are becoming an unsustainable environmental issue. For an adequate use of hydrothermal basalt in agriculture as soil remineralizer, it is fundamental to know the material's mineralogy and geochemical variability. This study aims to evaluate the mineralogical and geochemical variability of the basalt from five mines at two positions (near and far from the geodes) in different size fractions to discuss their potential use in agriculture. X-ray diffraction (XRD), X-ray fluorescence (XRF) and petrographic analyses of thin sections were used. Petrographic and mineralogical analyses showed similar compositions for the rocks, consisting of plagioclases, pyroxenes, and opaque minerals with apatite as an accessory mineral. The rock samples located near the amethyst geodes presented slightly higher clay mineral contents than the distant ones. The clay mineralogy was composed of smectite and celadonite. The subfractions preserved the characteristics of the original material. Small geochemical and mineralogical variations were observed in the hydrothermal basalts regardless of the positions and the fraction sizes studied. These characteristics confer this material a high potential for use in agriculture as a soil remineralizer. This approach contributes both to solving an environmental issue associated with geode exploitation and to create an alternative for soil fertilization. Graphical abstract: Highlights: Amethyst geode exploitation generates large amounts of waste (hydrothermal basalt tailings). Chemical and mineralogical analyses were performed on different hydrothermal basalt samples. Low variability of basalt powders was observed in sample collect positions. Hydrothermal basalt powders present clays, clay minerals and nutrients usefully for plants.